Special feature: LIS. Middleware: what's the buzz? - Vail GR (Medical Laboratory Observer (MLO), 2006)
We need to redefine what middleware means for today's clinical laboratory so that its benefits are apparent. To do that, we need to understand why middleware came about and what it does.